Application of Chromatographic Methods in Forensic Examination of Wine Products - I. L. Kazantseva; V. V. Egorova; D. M. Osokin (Теория и практика судебной экспертизы)
. The article overviews the changes in the Russian legislation regarding the terminology and classification of wine products, which should be considered when solving diagnostic and classification problems within the framework of complex examinations (commodity expertise of food products and forensic examination of materials, substances and products of alcoholcontaining liquids). The authors stress the importance and relevance of chromatographic methods in wine products examination. They also present the results of testing a method for organic acids determination in wine using JetChrom liquid chromatograph. Some examples are given from expert practice regarding the use of the gas chromatographic methods for analyzing the composition of toxic micro-impurities of base alcohol liquids and the high-performance liquid chromatography method for analyzing the composition of organic acids of the objects under research.